Data Wise: a step-by-step guide to using assessment results to improve teaching and learning - Parker, Kathryn; City, Elizabeth (Cambridge: Harvard Education Press, 2005)
Contents: Organizing for collaborative work,building assessment literacy, creating a data overview, digging into data,examining instruction, developing an action plan, planning to assess progress, acting and assessing, roles for the district central office.
Include appendix
Keywords: Enseñanza - Profesor